2017
DOI: 10.21767/2348-1927.1000103
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Approach toward Maize Production: Effectiveness of Farm Yard Manure and Urea N

Abstract: Maize (Zea mays L.) is grown in north western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…This continuous synthetic fertilization had further decreased the organic matter contents of the soil and rendered the soil as non‐sustainable. Beside commercial fertilization, the other various fertilization approaches (i.e., the use of manure, crop residue, on‐farm compost or commercial compost) can be used both as sole source or combined with synthetic fertilizers for sustainable production in the study area (Ibrahim and Khan, 2017; Khan et al, 2017). In this article we are addressing one of the approach i.e., integrated use of nutrients effects on soil bulk density, C and N stocks and allied C sequestration in a very poor soil in the north‐western Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This continuous synthetic fertilization had further decreased the organic matter contents of the soil and rendered the soil as non‐sustainable. Beside commercial fertilization, the other various fertilization approaches (i.e., the use of manure, crop residue, on‐farm compost or commercial compost) can be used both as sole source or combined with synthetic fertilizers for sustainable production in the study area (Ibrahim and Khan, 2017; Khan et al, 2017). In this article we are addressing one of the approach i.e., integrated use of nutrients effects on soil bulk density, C and N stocks and allied C sequestration in a very poor soil in the north‐western Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Returning organic residue to the soil and N fertilization can increase SOC (Khan et al, 2018) and TN both in tilled and non‐tilled systems (Somerville et al, 2018). The small farmers keep their cattle at home and/or farm and thus the available farmyard manure (FYM) from these cattle would be a useful source of readily available nutrients at the farm level (Khan et al, 2017; Muhammad et al, 2018). Due to increasing demand for dairy products, an increase in FYM production is expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Khyber Pakhtunkhwa, it is the 2 nd most important and grown crop after wheat (Triticum aestivum L.), whereas in Pakistan its rank is 3 rd . Maize crop has multiple uses like it is used as food, feed and raw materials for commercial product preparation (Khan et al, 2017). Pakistan economic survey show that maize was planted on 1.40 million ha land and produced 7.88 million tons with 5121 kg ha -1 average yield (MNSF&R, 2020).…”
mentioning
confidence: 99%
“…These results are in line with findings of Cisse et al (2019) which determine that maize harvest index is influenced by inorganic and organic combination, and also application of 30 m 3 per ha swine manure and 20 kg per ha biofertilizers can reduce until 50% of the NPK use without declining grain yields in North China. Adhikary et al (2020) and Khan et al (2017) reported that nitrogen usage from mineral nitrogen and manure increases total N in soil. Cisse et al (2019) concluded that 30 m 3 per ha pig manure and 20 kg per ha bio-fertilizers usage reduces chemical fertilizer need of at least 50% grain yields in the North China Plain.…”
Section: Crop Productionmentioning
confidence: 99%